PERAN PEMERINTAH DAN ADAPTASI PELAKU USAHA UMKM KAIN ULOS PASCA KRISIS MONETER 1998: STUDI KASUS KOTA PEMATANGSIANTAR - Nikolas Supriyanto; Tio Dora Br Tambunan; Lestari Dara Cinta Utami Ginting (Juremi: Jurnal Riset Ekonomi, 2024)
Ulos cloth is an integral part of the Batak ethnic cultural identity. In addition to being an important part of customs, Ulos cloth is also used in various events such as birth, marriage, welcoming guests, death, and others. Each type of Ulos cloth has a motif that is full of symbolic meaning and honor. The Ulos fabric trade, which is currently centered in Pematangsiantar City, has experienced significant growth due to the strategic position and dominance of the Batak Ethnicity in the city. It is interesting to examine how Ulos cloth contributes to the Creative Economy of MSMEs, especially as a cultural identity, especially after the 1998 Monetary Crisis. The crisis had far-reaching socio-economic impacts, and directly affected the Ulos cloth trade in Pematangsiantar City. This research aims to observe the phenomenon using historical research methodology with four stages: Heuristics (data collection), Verification (data filtering), Interpretation (data analysis), and Historiography (historical narrative preparation). The data used comes from two main sources, namely oral data from interviews with Ulos business actors in Pasar Horas Kota Pematangsiantar and written data from reliable sources such as books and journals. This historical research methodology aims to reveal the influence of Ulos Cloth MSMEs on the economic development of Pematangsiantar City after the 1998 Monetary Crisis. It is hoped that this research can provide a comprehensive picture of the condition of the Ulos cloth trade in Pematangsiantar City after the 1998 Monetary Crisis, as well as provide new insights into the contribution of Ulos Cloth MSMEs to the local economy